2020
DOI: 10.26452/ijrps.v11i4.3802
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative regional scalp block versus intraoperative intravenous fentanyl for attenuating intraoperative surgical stress response to supratentorial craniotomy in adult patients under general anaesthesia

Abstract: During brain tumour resection a lot of noxious stimuli are released resulting in a significant hemodynamic and stress response, its control is challenging during anaesthesia, and can be evaluated by monitoring blood pressure (BP), heart rate (HR) Attenuating autonomic cardiovascular responses to pain resulting from skull pinning, skin incision, and craniotomy are considered significant benefits of Regional Scalp Block (RSB) in addition to reducing postoperative analgesic requirements. This study aims to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…41,46,47,49 These analgesic effects were also present in RCTs using basic analgesics. 45,47,49 Another RCT compared SNB with intra-operative DEX infusion. The pain scores were lower up to 2 h postoperatively, but the differences were not clinically significant.…”
Section: Scalp Nerve Blockmentioning
confidence: 82%
See 3 more Smart Citations
“…41,46,47,49 These analgesic effects were also present in RCTs using basic analgesics. 45,47,49 Another RCT compared SNB with intra-operative DEX infusion. The pain scores were lower up to 2 h postoperatively, but the differences were not clinically significant.…”
Section: Scalp Nerve Blockmentioning
confidence: 82%
“…[41][42][43][44][45][46][47][48][49] Eight out of the nine demonstrated that single injection SNB reduced pain scores, with a lasting effect from 2 to 48 h postoperatively, compared with placebo. [41][42][43][44][45][46][47]49 SNB also reduced postoperative opioid consumption in four studies. 41,46,47,49 These analgesic effects were also present in RCTs using basic analgesics.…”
Section: Scalp Nerve Blockmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 955 studies, 22 RCTs met the inclusion criteria (Figure 1). 14,32-52 ClinicalTrials.gov search revealed 22 protocols; 13 completed ( Supplemental Materials, Appendix B , http://links.lww.com/NEU/D625). All trials meeting the inclusion criteria were either already captured or not yet available.…”
Section: Resultsmentioning
confidence: 99%